Working with budget and funding options to make open access journals sustainable - Nicole Waidlein; Marcel Wrzesinski; Frédéric Dubois; Christian Katzenbach (Alexander von Humboldt Institut für Internet und Gesellschaft (HIIG), 2021)
Within the realm of electronic publishing, journals are plenty and their publishing models vary greatly. A segment most in line with fair and transparent open access principles are journals that were born open access, are scholar-led, and do not levy any fees on authors or readers. But while promising for increasing access to quality research and furthering bibliodiversity (i.e., variety of content, publication formats and publishing institutions), a survey we did in Germany in 2020 suggests that many of the journals in that segment face the threat of extinction. This white paper provides preliminary answers to the monetary challenge by evaluating possible financing models, discussing their applicability, and facilitating the transferability of these findings by including a short case study of Internet Policy Review-an international, peer-reviewed diamond open access journal.
Keywords: 330; Open access; Scholar-led; Business models; Sustainability; Funding; Small sciences